IS IT APPROPRIATE TO INITIATE PALLIATIVE CARE IN A PAEDIATRIC INTENSIVE CARE UNIT (PICU)?. Issue 2 (1st June 2013) - Crowe, L; Herbert, A; Mattke, A
Abstract : Background: Paediatric Palliative care is being redefined as medical technology and advancements can at times 'make death an option'. Children with life limiting conditions can now be on palliative care for years making the boundaries for limitations challenging. The team at the Mater Children's PICU work closely with the Paediatric Palliative Care Service and are a major source of early referrals for children with complex and life limiting conditions. Aim: Review the referral process for children to the Queensland paediatric palliative care service from PICU. Methods: Using our electronic chart system we identified 54 patients who had been referred to the palliative care service since 2008. Using thematic analysis we reviewed who initiated discussions, what patient descriptors were associated with referral, common themes and outcomes. Results: The majority of children referred had complex medical needs. PICU referral to Palliative Care introduced a greater focus on quality of life and the concept of limiting aggressive care. Discussion: PICU is often viewed as an acute medical environment and not one where palliation discussions for complex long term patients occur. However we found that due to the critical nature of PICU it is often time for a holistic review of the medical history; child and family goals and a focus on quality of life. Conclusion: The PICU team have extensive experience in talking about end of life issues and are ideally placed to work with the Palliative Care Service to initiate referrals, enhance management of subsequent crises and maximise quality of life in PICU and on discharge.